General and Efficient Protocol for Formylation of Aromatic and Heterocyclic Phenols - Skonieczny, Kamil; Charalambidis, Georgios; Tasior, Mariusz; Krzeszewski, Maciej; Kalkan-Burat, Ayfer; Coutsolelos, Athanassios G.; Gryko, Daniel T. (Synthesis, 2012)
A convenient, general procedure for formylation of diverse range of phenols with the Duff protocol has been developed. The procedure gives dialdehydes when possible.
Keywords: aldehydes; arenes; electrophilic aromatic substitution; heterocycles; phenols